Gaseous carbonation of cementitious backfill for geological disposal of radioactive waste: Nirex Reference Vault Backfill. (July 2019) - Collier, Nicholas C.; Heyes, David W.; Butcher, Ed J.; Borwick, Jason; Milodowski, Antoni E.; Field, Lorraine P.; Kemp, Simon J.; Mounteney, Ian; Bernal, Susan A.; Corkhill, Claire L.; Hyatt, Neil C.; Provis, John L.; et al.
Abstract: The ability of Nirex Reference Vault Backfill (NRVB), a cement backfill material, to capture carbon dioxide from Intermediate Level Radioactive waste packages after repository backfilling, has been assessed. Large-scale trials assessed the physical and chemical reaction of carbon dioxide with the hardened backfill grout. A carbonation front, radial in nature, was observed extending into the grout and three distinct regions were identified in the hardened grouts. A carbonated region, a carbonation front, and a partially carbonated zone were discerned. Potassium, and to a lesser extent sodium, were concentrated in the carbonated region just behind of the main reaction front. The area just ahead of the carbonation front was enriched in both sulphur and aluminium, while sulphur was found to be depleted from the carbonated material behind the main reaction front. Within the main carbonated region, virtually all of the hydrated cement phases were found to be carbonated, and carbonation extended throughout the grout, even within material indicated by phenolphthalein solution to be uncarbonated. Importantly, carbonation was observed to impact both the mineral assemblage and porosity of the cement backfill; it is therefore important to understand these characteristics in terms of the long term evolution of NRVB and its groundwater buffering safety function within the geological disposal facility near-field. Highlights: Carbonation of a potential backfill resulted in fully, partially and uncarbonated zones. Potassium (and to a lesser extent sodium) were concentrated in the carbonated region. Sulphur and aluminium were found to be enriched just ahead of the carbonation front. Carbonation impacted the porosity and mineral assemblage of the backfill material.